2006
DOI: 10.2353/ajpath.2006.050435
|View full text |Cite
|
Sign up to set email alerts
|

EphrinA1 Inhibits Vascular Endothelial Growth Factor-Induced Intracellular Signaling and Suppresses Retinal Neovascularization and Blood-Retinal Barrier Breakdown

Abstract: The Eph receptor/ephrin system is a recently discovered regulator of vascular development during embryogenesis. Activation of EphA2, one of the Eph receptors, reportedly suppresses cell proliferation and adhesion in a wide range of cell types, including vascular endothelial cells. Vascular endothelial growth factor (VEGF) plays a primary role in both pathological angiogenesis and abnormal vascular leakage in diabetic retinopathy. In the study described herein, we demonstrated that EphA2 stimulation by ephrinA1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
44
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(45 citation statements)
references
References 43 publications
1
44
0
Order By: Relevance
“…Also, vasoinhibins block increased retinal vasopermeability induced by the intravitreal injection of VEGF. However, the concentrations of VEGF required by us (260 nM) and by others (30 nM) (35) to increase retinal vasopermeability are much higher than the VEGF levels detected in the vitreous of diabetic patients (220 pM, ref. 29; and 5.8 pM, present study) or of streptozotocininduced diabetic rats (225 pM) (34).…”
Section: Discussionmentioning
confidence: 96%
“…Also, vasoinhibins block increased retinal vasopermeability induced by the intravitreal injection of VEGF. However, the concentrations of VEGF required by us (260 nM) and by others (30 nM) (35) to increase retinal vasopermeability are much higher than the VEGF levels detected in the vitreous of diabetic patients (220 pM, ref. 29; and 5.8 pM, present study) or of streptozotocininduced diabetic rats (225 pM) (34).…”
Section: Discussionmentioning
confidence: 96%
“…In cultured bovine retinal endothelial cells, VEGF induces VEGFR-2 receptor phosphorylation and activation of the downstream signaling cascade including protein kinase C-extracellular signal-regulated kinase 1/2 [29]. In addition, a study in rats demonstrated that intraocular injection of VEGF increases retinal vascular permeability and that activation of the VEGF-VEGF receptor signaling pathway contributes to a breakdown of the blood-retinal barrier [29]. Furthermore, inhibition of VEGF-VEGFR-2 signaling blocks changes of intercellular tight junctions (including zonula occludens-1 (ZO-1), ZO-2, and occludin) in retinal endothelial cells and prevents a blood-retinal barrier breakdown [30].…”
Section: Discussionmentioning
confidence: 99%
“…In cultured human retinal endothelial cells, activation of VEGFR-1 and VEGFR-2 causes disruption of tight junctions by reducing occludin levels, and the VEGF receptor signaling pathway plays a key role in the development of blood-retinal barrier dysfunction [28]. In cultured bovine retinal endothelial cells, VEGF induces VEGFR-2 receptor phosphorylation and activation of the downstream signaling cascade including protein kinase C-extracellular signal-regulated kinase 1/2 [29]. In addition, a study in rats demonstrated that intraocular injection of VEGF increases retinal vascular permeability and that activation of the VEGF-VEGF receptor signaling pathway contributes to a breakdown of the blood-retinal barrier [29].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, there is evidence to suggest that PI3K-mediated activation of Rac1 GTPase may be partially regulated through Vav2 and Vav3 guanine nucleotide exchange factors (Hunter et al, 2006). Another study by Ojima and colleagues using bovine retinal endothelial cells (BRECs) demonstrated that VEGF-induced extracellular regulated kinase 1 and 2 (Erk1/2) and Akt phosphorylation was inhibited by pretreatment with ephrin-A1 (Ojima et al, 2006). Furthermore, this inhibition was found to reduce the effects of VEGF-stimulated endothelial cell migration, tube formation, and proliferation.…”
Section: The Role Of Epha2 and Ephrin-a1 In Adult Angiogenesismentioning
confidence: 99%